2023
DOI: 10.3390/antiox12061275
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Diabetic Properties of Olive (Olea europaea) Leaf Extracts: In Vitro and In Vivo Evaluation

Hanem M. M. Mansour,
Ashraf A. Zeitoun,
Hagar S. Abd-Rabou
et al.

Abstract: (1) Objective: The main objective of the current study was to evaluate in vitro and in vivo an antioxidant property of three genotypes of olive leaf extract (OLE) (picual, tofahi and shemlali), and furthermore to assess potential activity in the treatment and/or prevention of diabetes mellitus type II and related implications. (2) Methodology: Antioxidant activity was determined by using three different methods (DDPH assay, reducing power and nitric acid scavenging activity). In vitro α-glucosidase inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Tiny amounts of the OLE revealed a high scavenging activity against DPPH • and ABTS • radicals: Tofahy and Shemlali’ OLE extracts effectively scavenged 50% of DPPH • (IC 50 = 35.44 ± 0.45 and 30.39 ± 0.22 μg/mL, respectively) and ABTS • (IC 50 = 13.91 ± 0.63 and 11.99 ± 0.22 μg/mL, respectively). The high scavenging activity could be due to the high concentrations of oleuropein, rutin, benzoic acid, salicylic acid, p-hydroxybenzoic acid, and ellagic acid [ 63 ]. We obtained a higher scavenging activity in the present study than Urzúa et al [ 25 ], who reported that 0.15 mg/mL scavenged 50% of DPPH • .…”
Section: Resultsmentioning
confidence: 99%
“…Tiny amounts of the OLE revealed a high scavenging activity against DPPH • and ABTS • radicals: Tofahy and Shemlali’ OLE extracts effectively scavenged 50% of DPPH • (IC 50 = 35.44 ± 0.45 and 30.39 ± 0.22 μg/mL, respectively) and ABTS • (IC 50 = 13.91 ± 0.63 and 11.99 ± 0.22 μg/mL, respectively). The high scavenging activity could be due to the high concentrations of oleuropein, rutin, benzoic acid, salicylic acid, p-hydroxybenzoic acid, and ellagic acid [ 63 ]. We obtained a higher scavenging activity in the present study than Urzúa et al [ 25 ], who reported that 0.15 mg/mL scavenged 50% of DPPH • .…”
Section: Resultsmentioning
confidence: 99%
“…Despite different results for the antioxidant activity of olive leaf extracts, the comparison with these is difficult due to the various experimental conditions, methods, and plant matrix used. Mansour et al [40] found an IC50 of approximately 50 μg/mL in aqueous olive leaf non-enriched extracts. This higher antioxidant activity is probably related to the different phytochemical profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that there are many studies concerning the in vitro antioxidant activity of OLs extracts [ 52 , 53 , 54 , 55 , 56 ], less is known about hydrolyzed extracts. In the first case, the bioactivity of the extracts is mainly exerted due to OLE, as the main phenol in OLs, while after hydrolysis, the main drastic component is HT.…”
Section: Discussionmentioning
confidence: 99%